Is there evidence of gender preference for offspring in France? Examining the predilections of native women and immigrant women from Asia and Africa - Sehar Ezdi; Sabrina Pastorelli (Comparative Population Studies (CPoS), 2021)
This paper investigates gender preferences for offspring within the native French population and among immigrants from North Africa, Sub-Saharan Africa, Turkey and Vietnam-Cambodia-Laos in France by combining the Family and Housing Survey (2011) and the Trajectories and Origins Survey (2008). In so doing, it is the first paper to examine the persistence (or lack thereof) of gender preferences among immigrants in France. This allows the findings of the paper to serve as a tool for monitoring the immigrant integration process in the country. Using (multilevel) logistic regressions to examine transitions to second and third child births contingent upon gender of existing children and by migration status provides two main results. First, regarding evidence of gender preferences, the results show: mixed gender preferences and weak daughter preference among native French women when transitioning to the third parity; mixed gender preferences among second-generation Turkish immigrant women when transitioning to the third parity; and a daughter preference for second-generation North African, Sub-Saharan African and Vietnamese-Laos-Cambodian immigrant women when transitioning to the third parity. Second, for the immigrant sample, these preferences emerge in the face of declining fertility, across subsequent generations of immigrants, and on average as a deviation from their country of origin gender preferences. This not only points to the malleability of gender preferences for offspring but also lends credence to both the selection and adaptation hypotheses in explaining immigrant integration in France.
urn:nbn:de:bib-cpos-2021-11en3
Keywords: 300; Comparison; Fertility decline; Immigrants; Integration; Migration status; Parental gender preferences; Transitions